Nitrate and nitrite reduction at high pH in a cementitious environment by a microbial microcosm. (October 2018) - Durban, Nadège; Rafrafi, Yan; Rizoulis, Athanasios; Albrecht, Achim; Robinet, Jean-Charles; Lloyd, Jonathan R.; Bertron, Alexandra; Erable, Benjamin
Abstract: The possible release of oxyanions, such as nitrate, from radioactive waste repositories may influence redox-conditions of the near field environment and thus promote mobility of some redox sensitive radionuclides. The fate of dissolved oxyanions will be significantly conditioned by microbial activities, if present in the aqueous interstitial phase of a waste cell. This study investigates microbial nitrate reduction in a cementitious environment. A consortium of microorganisms was used, an inoculum prepared with sediments collected from a former lime works site, characterized by a pH of pore water of 11–12. The biomass was acclimated to cement leachate supplemented with nitrate, acetate and yeast extract. According to experiments performed in closed and in dynamic systems, the microbial consortium was adapted to reduce nitrate and nitrite in a cementitious, anaerobic environment (pH 11, with and without hardened cement paste and leachate). Although, nitrite accumulation was observed in close system and temporally in dynamic system. The rate of nitrate reduction was between 0.12 and 0.75 mM/h with incoming nitrate concentrations between 6 and 48 mM, respectively. The microorganism diversity and the biofilm present on the hardened cement paste helped maintain microbial activity in all of the conditions simulating cementitious environments. Highlights: Microbial denitrification at an initial pH 11 in a cementitious environment. Several microorganisms from the consortium can colonise cementitious material. Nitrate concentration below 50 mM was not toxic for denitrifying biomass. Nitrite accumulation observed only in batch reactor. Microbial diversity can promote the apparent microbial rate of denitrification.